The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1056/nejm198501313120504
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Hypertrophic Cardiomyopathy of the Elderly

Abstract: Using echocardiography, we identified 21 patients with a syndrome that included severe concentric cardiac hypertrophy, a small left ventricular cavity, and supernormal indexes of systolic function without concurrent medical illness or ischemic heart disease. Thirteen of the patients presented with dyspnea or chest pain. All patients studied had a history of hypertension and were compared with normotensive controls matched for age and sex. The patients were elderly (mean age, 73.3 years), predominantly female (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
1
9

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(182 citation statements)
references
References 25 publications
6
166
1
9
Order By: Relevance
“…Therefore, authors 2 proposed that this condition might be better termed HCM with hypertension rather than hypertensive HCM as this syndrome was previously labelled by Topol et al 3 Our findings support this proposal, because we have shown that this asymmetric LVH pattern (common for isolated HCM) was present in both younger and older HCM patients with hypertension. Moreover, asymmetric distribution of LVH aggravated with increasing age in HCM with hypertensive patients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, authors 2 proposed that this condition might be better termed HCM with hypertension rather than hypertensive HCM as this syndrome was previously labelled by Topol et al 3 Our findings support this proposal, because we have shown that this asymmetric LVH pattern (common for isolated HCM) was present in both younger and older HCM patients with hypertension. Moreover, asymmetric distribution of LVH aggravated with increasing age in HCM with hypertensive patients.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies [1][2][3][4] provided conflicting data concerning which type of LVH pattern (asymmetric or concentric) predominated in HCM with hypertension patients. In the most populous study of Lewis and Maron, 1 the predominance of the asymmetric LVH pattern and the magnitude of asymmetry was similar between normotensive and hypertensive HCM patients in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCM has been reported to have some variants with atypical features in elderly women and one of them is characterized by severe concentric left ventricular hypertrophy with a history of systemic hypertension and abnormal left ventricular diastolic function; 12 another is characterized by obstructive HCM with submitral annular calcification. 13 However, the present case did not have either of these 2 variations.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several studies using echocardiography have demonstrated deterioration in left ventricular diastolic properties in diabetic patients. [6][7][8][9] RV function has proven to be of importance for risk stratification in heart failure and is associated with sudden death and exercise limitation . 10 RV function has not been studied in depth yet in diabetic patients although the RV has an important contribution to the overall cardiac function .…”
Section: Introductionmentioning
confidence: 99%